THE DATA-ETHICS PARADOX: RECONCILING MARKETING PERSONALIZATION WITH CONSUMER PRIVACY IN DIGITAL OPERATIONS - Sowmya Kotha, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This article examines the complex intersection of marketing operations and consumer privacy in the era of data-driven personalization. Through a mixed-methods approach combining quantitative analysis of industry practices (n=245) and qualitative assessment of consumer perspectives (n=48), we investigate the ethical implications of advanced data collection techniques in modern marketing operations. Our findings reveal a significant disconnect between marketing practitioners' drive for personalization and consumers' privacy expectations, with 73% of consumers expressing concern about data collection practices while simultaneously demonstrating preference for personalized experiences. We propose a novel ethical framework for data collection that emphasizes three key pillars: transparent disclosure, granular consent mechanisms, and consumer data sovereignty. The article contributes to both theoretical understanding and practical application by developing actionable guidelines for marketing operations that balance innovation with privacy protection. The findings suggest that organizations implementing the proposed framework demonstrate a 42% increase in consumer trust metrics while maintaining personalization effectiveness. This article advances the discourse on digital marketing ethics and provides a roadmap for future research into sustainable, privacy-conscious marketing practices in an increasingly data-driven landscape.